A Small Impact Crater in the Dhofar Mountains, Sultanate of Oman: Surface Expression from Satellite Imagery and Cues from the Profiles of ICESat‑2 Photons - Dandabathula, Giribabu; Ghatage, Omkar Shashikant; Roy, Subham; Bera, Apurba Kumar; Srivastav, Sushil Kumar (Earth and Planetary Science, 2025)
This study discovered a surface expression of one small impact crater on the slopes of the Dhofar Mountains, Sultanate of Oman. This research utilized high‑resolution satellite imagery, a digital elevation model, and ICESat‑2 photon data to determine the geomorphological features of the impact crater. Elevation profiles from the ICESat‑2 photons highlighted the crater’s rim structure with high precision. Also, the structure of this impact crater was crosschecked with a confirmed crater on similar geological settings on Mars using HiRise imagery and numerical simulations. Additionally, a scaled sandbox experiment ensured the simulation of the impact mechanism on slopes. The identified impact crater is a simple type (non‑complex) with a nearly bowl‑shaped depression having a raised rim structure and a maximum diameter of ∼259 m. However, bearing its location on a sloped terrain and at the edge of the gorge’s cliff‑top, this elliptical crater remained crescent, with the deepest point shifted downhill. Notably, features related to the crater’s structure, such as the rim, the floor’s deepest point, and a tongue‑like landslide at the downhill, are consistent with the numerical simulations and corroborate the results from the lab‑based experiments. The crater’s ellipticity and depth‑to‑diameter ratio agree with the mechanisms involved in impact crater formation on slopes. This impact crater is one of the rarest on Earth, uniquely located on sloped terrain, and is the first to be reported through this article. ER